THE ASSOCIATION OF INTERGENERATIONAL RELATIONSHIPS WITH THE WELL-BEING OF OLDER ADULTS IN RURAL CHINA - Liu, M (Innov Aging, 2018)
Intergenerational relationships (IR) have been studied as a homogeneous concept in existing literature, while its nature is multidimensional, including structural, emotional, monetary, and instrumental aspects. Moreover, few studies have examined the interchangeabilities of these dimensions (e.g., time-for-money exchange in grandparenting), how the expectations for each type of relationships change at different stages of life, how the provision and acceptance of different kinds of intergenerational support associates with the well-being of older adults, and under which family structure each type of relationships has the greatest connections. Chinese society has been experiencing rapid population aging and massive rural to urban migration, which greatly affected IR in China, especially rural areas. Using data from the Longitudinal Study of Older Adults in Anhui Province, China, six waves of data collected from 2001 to 2015, five presentations in this symposium scrutinized the correlations of IR on diverse aspects of the well-being (e.g., social isolation, cognitive ability, death anxiety, life satisfaction) of older adults in rural China. Specifically, one study examined how death anxiety is affected by family related factors, another study investigated the change of IR before death of older adults, one presentation explored how living arrangement could moderate the effects of IR on life satisfaction while another presentation examined the impact of caregiving for grandchildren on grandparents’ cognitive health, and remittances from migrant children as a resource that potentially buffers the impact of caregiving, and the last paper studied the link between different aspects of IR on the extent of social isolation.